Toward an old-growth concept for grasslands, savannas, and woodlands - Veldman, Joseph W; Buisson, Elise; Durigan, Giselda; Fernandes, G Wilson; Le Stradic, Soizig; Mahy, Gregory; Negreiros, Daniel; Overbeck, Gerhard E; Veldman, Robin G; Zaloumis, Nicholas P; Putz, Francis E; Bond, William J (Frontiers in ecology and the environment, 2015)
We expand the concept of "old growth" to encompass the distinct ecologies and conservation values of the world's ancient grass-dominated biomes. Biologically rich grasslands, savannas, and open-canopy woodlands suffer from an image problem among scientists, policy makers, land managers, and the general public, that fosters alarming rates of ecosystem destruction and degradation. These biomes have for too long been misrepresented as the result of deforestation followed by arrested succession. We now know that grassy biomes originated millions of years ago, long before humans began deforesting. We present a consensus view from diverse geographic regions on the ecological characteristics needed to identify old-growth grasslands and to distinguish them from recently formed anthropogenic vegetation. If widely adopted, the old-growth grassland concept has the potential to improve scientific understanding, conservation policies, and ecosystem management.